Potopisno pripovedništvo za turizem in znamčenje mest: Metodologije pisanja o urbanih prostorih - Mansfield , Charlie; Jasna Potočnik Topler, Jasna (University of Maribor Press, 2026)
Travel Writing for Tourism and City Branding: Urban Place-Writing Methodologies. The monograph contributes to the professionalisation of travel writing. Its approach establishes a new connection between tourism and city branding, which will encourage new travel writers and bloggers to produce thoughtful, high-quality content. The book demonstrates that literary travel writing is a research process that an author–researcher can apply in spaces where value is created. This research process extracts, preserves and communicates that value, while also serving the writer as a tool for in-depth exploration of place. Travel writing as research is presented as a methodological practice that researchers can learn and apply in their projects, both in academic contexts and in the commercial context of city branding. Examples of literary travel writing from the authors’ research projects are examined, and their effects are further analysed. The monograph contributes new insights, also by including research findings on urban spaces obtained through this new method.